Exercise in patients with hip osteoarthritis – effects on muscle and functional performance: A randomized trial. - Bieler, Theresa; Kristensen, Asker Lau Røn; Nyberg, Mette; Magnusson, S. Peter; Kjaer, Michael; Beyer, Nina (Physiotherapy Theory & Practice, 2022)
It is believed that clinical management of osteoarthritis should address muscle weakness to improve physical function and prevent disability and frailty This sub-study investigated the effects of supervised progressive resistance training (RT), supervised Nordic Walking (NW), and unsupervised home-based exercise (HBE) on muscle and functional performance; and associations between these exercise-induced changes in persons with hip osteoarthritis. Forty-two patients with hip osteoarthritis were recruited from a larger RCT (NCT01387867). All the groups (RT, n = 15; NW, n = 12; HBE, n = 15) exercised 1 h 3 times/week for 4 months. Quadriceps cross-sectional area (QCSA, MRI-determined); quadriceps strength (QMVC); leg extensor power (LEP); functional performance (chair stands (30sCS); stair climbs (TSC); and 6-minute walk (6MWT)) were assessed at baseline and 4 months. Per protocol analyses (one-way ANOVA and Bonferroni test) showed significant between-group differences for improvements in QCSA in the most symptomatic leg favoring RT versus NW (2.3 cm2, 95% CI [0.6, 3.9]) and HBE (2.3 cm2 [0.8, 3.9]); and 30sCS (1.8 repetitions [0.2–3.3]), and 6MWT (35.1 m [3.5–66.7]) favoring NW versus HBE. Associations existed between exercise-induced changes in QCSA and QMVC (r = 0.366, p =.019) for the most symptomatic leg and between changes in 6MWT and QMVC (r = 0.320, p =.04) and LEP (r = 0.381, p =.01), respectively, for the least symptomatic leg. Resistance training appeared effective for improving muscle mass, but less effective for improving muscle strength, power, and functional performance. Only exercise-induced changes in muscle strength and power of the least symptomatic leg, not the most symptomatic leg, were related to changes in functional performance.